Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.08.26.21262708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child and caregiver mental health during 12 months of the COVID-19 pandemic in Australia: findings from national repeated cross-sectional surveys

Abstract: There are urgent calls for research into the mental health consequences of living through the COVID-19 pandemic. We describe caregiver and child mental health over 12 months using Australia's only nationally representative, repeated cross-sectional survey of caregivers with children (0-17 years). N=2020 caregivers in June 2020, N=1434 in September 2020, and N=2508 in July 2021 provided data. Caregivers rated their mental health (Kessler-6), and impacts of the pandemic on their own and their children's mental h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Olive et al ( 2022 ) found children experiencing COVID‐related declines in physical activity and increased recreational screen time were experiencing greater sleep disruption, elevated anxiety and irritability symptoms. The mental health of parents and carers, particularly those experiencing socioeconomic adversity, also declined (see Price et al, 2022 ). In this context, mental health services that are equipped to respond to children are essential.…”
Section: Covid ‐19 Responses and Opportunities To Access Ser...mentioning
confidence: 99%
See 1 more Smart Citation
“…Olive et al ( 2022 ) found children experiencing COVID‐related declines in physical activity and increased recreational screen time were experiencing greater sleep disruption, elevated anxiety and irritability symptoms. The mental health of parents and carers, particularly those experiencing socioeconomic adversity, also declined (see Price et al, 2022 ). In this context, mental health services that are equipped to respond to children are essential.…”
Section: Covid ‐19 Responses and Opportunities To Access Ser...mentioning
confidence: 99%
“…Important surveys were adopted or adapted during 2020 to assess children's mental health and well‐being (Price et al, 2022 ; Westrupp et al, 2020 ) and to better understand the impacts of the pandemic on mental health. Significantly, however, survey respondents were parents and carers, rather than children.…”
Section: Covid ‐19 Responses and Opportunities To Access Ser...mentioning
confidence: 99%